PESANTREN, NASIONALISME, DAN MULTIKULTURALISME DI INDONESIA - Ahmad 'Ubaydi Hasbillah (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2015)
Religion and state for some countries deemed unable to work in harmony. At the same time, some other countries actually believe that religion can strengthen the integrity and resilience of the country. The experience of a country affects the paradigm of the relation between religion and the state, of course. However, experience alone is not enough if it is not supported by reliable human resources. Therefore, this study would like to assert that the development of nationalism is the main task of religious education. Religion and state must be properly managed through an established educational system in order to foster the spirit of nationalism. Through a historical survey and educational curriculum, Pesantren proven to contribute greatly to the independence of Indonesia. Transnationalism displayed by some of the pesantren alumni are sourced from outside. If Robert Jackson (2004) offers a model of